Comparative efficacy and discontinuation of dimethyl fumarate and fingolimod in clinical practice at 24-month follow-up. Issue 3 (August 2017) - Hersh, Carrie M; Love, Thomas E; Bandyopadhyay, Anasua; Cohn, Samuel; Hara-Cleaver, Claire; Bermel, Robert A; Fox, Robert J; Cohen, Jeffrey A; Ontaneda, Daniel
Background: Dimethyl fumarate and fingolimod are oral disease-modifying therapies approved to treat relapsing multiple sclerosis. Prior observational studies and our previous 12-month investigation showed comparable clinical efficacy. Objective: The purpose of this study was to assess real-world efficacy and discontinuation of dimethyl fumarate and fingolimod over 24 months in patients with multiple sclerosis. Methods: Patients treated with dimethyl fumarate ( n  = 395) or fingolimod ( n  = 264) completed 24-month follow-up in a large academic multiple sclerosis center. Discontinuation rates and measures of disease activity were compared after propensity score weighting. The primary outcome was on-treatment annualized relapse rate ratio. Other measures included rate of drug discontinuation and brain magnetic resonance imaging activity defined as new T2 and/or gadolinium-enhancing lesions. Results: Propensity score weighting showed excellent covariate balance. At 24 months, dimethyl fumarate demonstrated comparable annualized relapse rate (rate ratio = 1.45, 95% confidence interval 0.53–3.99) and brain magnetic resonance imaging activity (odds ratio = 1.38, 95% confidence interval 0.83–2.32). Dimethyl fumarate patients discontinued therapy earlier compared to fingolimod (hazard ratio = 1.40, 95% confidence interval 1.11–1.77) and were more likely to discontinue therapy due to intolerability (odds ratio = 1.98, 95% confidence interval 1.18–3.23). Conclusion: Dimethyl fumarate and fingolimod had similar reductions in annualized relapse rate in clinical trials, and our real-world experience supports this observation. Dimethyl fumarate-treated patients had higher likelihood of early discontinuation, and this was mostly due to intolerability.